Outcomes for Māori participants in Housing First - Ombler, Jenny; Pehi, Tiria; Chun, Saera; Lawson-Te Aho, Keri; Jiang, Terence; Pierse, Nevil (The International Indigenous Policy Journal, 2025)
Indigenous homelessness in settler-colonial societies is determined by the ongoing impacts of colonization. Therefore, policies to address homelessness need to be effective for Indigenous populations whilst supporting ongoing systemic decolonization. Like other settler-colonial states, homelessness in Aotearoa New Zealand is disproportionately experienced by Māori, the Indigenous Peoples of Aotearoa. In Aotearoa NZ, Housing First has been funded by government to address chronic homelessness. Housing First is a rights-based approach to homelessness, centering around providing permanent housing and wraparound support, without preconditions such as sobriety or treatment compliance. As Housing First is a non-Indigenous North American model, the efficacy of the policy for Māori has been the subject of considerable discourse. In this paper, we present a pre- and post-housing analysis of outcomes for Māori clients of a Housing First programme in Kirikiriroa-Hamilton, using integrated government administrative data across health, justice and social welfare. Existing and systemic inequities are apparent in our results, but overall, the trajectory for Māori in Housing First is positive. Our findings support the efficacy of Housing First for Māori, if this occurs within the context of enduring systemic change.